Heuristic Algorithm For Nurse Scheduling Problem - Wee, Sze Ming (Universiti Malaysia Sarawak, (UNIMAS), 2023)
Since the Nurse Scheduling Problem (NSP) is mostly made up of numerous restrictions and assumptions, it is referred to as the Np-Hard problem. The Nurse Scheduling Problem (NSP) deals with allocating the nurses' required shifts over a scheduling period while taking into consideration several restrictions. Typically, the restrictions are determined by law, workplace traditions, and employee preferences. These restrictions are frequently separated into two categories: hard restrictions (mandated) and soft restrictions (should be satisfied as much as possible). All the strict requirements must be met by a workable roster. To resolve the nurse scheduling problem, a two-stage heuristic strategy has been used in this research. First, the simple shift assignment heuristic generates an initial schedule that satisfies all hard requirements. Second, by accounting for soft restrictions (nurse preferences), the sequential local search algorithm is used to enhance the initial schedules.